2019
DOI: 10.1155/2019/6212934
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation Impairs Mood Function by Disrupting the Resting-State Functional Network in a Rat Animal Model Induced by Lipopolysaccharide Challenge

Abstract: Background. Systemic inflammation impairs cognitive performance, yet the brain networks mediating this process remain to be elucidated. The purpose of the current study was to use resting-state functional magnetic resonance imaging (fMRI) to explore changes in the functional connectivity in a lipopolysaccharide- (LPS-) induced systemic inflammation animal model. Materials and Methods. We used the regional homogeneity (ReHo) method to examine abnormal brain regions between the control and LPS groups and then co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Besides, higher numbers of lymphocytes, monocytes, neutrophils, and platelets, and elevated levels of C-reactive protein, leptin, brain-derived neurotrophic factor, and matrix metalloproteinase-9 have been observed [71]. These findings supported the suggestion that persistent systemic inflammation is another factor contributing to brain dysfunction in GWI, as several studies have revealed that significant systemic inflammation leads to enduring cognitive dysfunction [[90], [91], [92], [93]]. Both hematogenous and neural pathways are likely involved in the interaction between systemic inflammation and the brain [94].…”
Section: Discussionmentioning
confidence: 66%
“…Besides, higher numbers of lymphocytes, monocytes, neutrophils, and platelets, and elevated levels of C-reactive protein, leptin, brain-derived neurotrophic factor, and matrix metalloproteinase-9 have been observed [71]. These findings supported the suggestion that persistent systemic inflammation is another factor contributing to brain dysfunction in GWI, as several studies have revealed that significant systemic inflammation leads to enduring cognitive dysfunction [[90], [91], [92], [93]]. Both hematogenous and neural pathways are likely involved in the interaction between systemic inflammation and the brain [94].…”
Section: Discussionmentioning
confidence: 66%
“…The patients with sepsis always suffered from severe multiple organ failure, and it was inconveniencing for them to nish the resting state MRI examination. By contrast, sepsis rats can be xed well by inhaling 2% iso urane during the MRI scan, therefore, they were suitable for cerebral function research by rs-fMRI [11]. Blood oxygenation level dependent (BOLD) fMRI detects changes of blood oxygen which was related to neuronal activity.…”
Section: Introductionmentioning
confidence: 99%